Development and validation of the diabetic self-management scale based on information-motivation-behavioral skills theory - Dai, Zhenwei; Jing, Shu; Liu, Xiaoyang; Zhang, Haoran; Wu, Yijin; Wang, Hao; Xiao, Weijun; Huang, Yiman; Fu, Jiaqi; Chen, Xu; Gao, Lei; Su, Xiaoyou (Frontiers in Public Health, 2023)
Background Self-management is important for the blood sugar control of middle-aged and elderly Type 2 diabetes mellitus (T2DM) patients, of which diet, exercise, and drug compliance are the most common components. The Information-Motivation-Behavioral Skills Model (IMB) has been widely used in health behavior management and intervention. Objective The purpose of this study is to develop and validate the Diabetic Self-Management Scale (DSMS) based on the IMB model. Methods Self-report survey data was collected from middle-aged and elderly T2DM patients in Zhongmu City, Henan Province, China in November 2021 using convenience sampling. The original DSMS was developed through a literature review and summary of previous similar scales using an inductive approach. Item modification was finished by a panel of specialists. Exploratory factor analysis and confirmatory factor analysis were used to evaluate the reliability, convergent validity, discriminant validity, and criterion validity of DSMS. Results 469 T2DM patients completed the questionnaire survey. The final DSMS consists of 22 items with three dimensions, including information (5 items), motivation (8 items), and behavior skills (9 items). The results of simple factor analysis showed that the KMO value was 0.839, Bartlett spherical test 2=3254.872, P<0.001. The results of confirmatory factor analysis showed that 2/df=2.261, RMSEA=0.073, CFI=0.937, TLI=0.930, and SRMR=0.096. The standardized factor loadings of 22 DSMS items were all above 0.6, and the CR values of 3 dimensions were all higher than 0.9. In addition, DSMS also showed good discriminant and criterion validity. Conclusion The 22-item DSMS has good reliability and validity, and can be used to make diabetic self-management assessment regarding diet, physical activity, and medication among middle-aged and elderly Chinese T2DM patients. DSMS is of moderate length and easy to understand. It can be promoted in China in the future to understand the self-management status of middle-aged and elderly T2DM patients in China.